HISTOCHEMICAL CHARACTERISTICS OF PLACENTAL TISSUE IN WOMEN WITH CARDIAC DEFECTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study examines histochemical alterations in placental tissue from women with congenital and acquired cardiac defects compared to healthy controls. Applying PAS-reaction, Alcian Blue, Van Gieson, Sudan III, and hematoxylin-eosin staining to 60 specimens, we identified significant reduction in trophoblast glycogen, increased fibrinoid deposition, basement membrane thickening, stromal fibrosis, and lipid accumulation, confirming measurable hypoxic placental injury.